The Effect of Vertical Earthquake Motion on Steel Structures Behaviour in Different Seismic Zones - Fatma Peker; Ercan Işık; Aydın Büyüksaraç (Journal of Advanced Research in Natural and Applied Sciences)
Each geographical location has its own seismicity and this affects the seismic behaviour of structures. In this study, four different settlements with different seismicity such as İzmir, Bitlis, Samsun and Konya were considered. Seismic risks and parameters for these provinces were compared. Analyses were carried out separately for a ten-storey steel building with the same structural characteristics in each of these provinces. The sample building model was created by considering the provisions of Principles for the Design, Calculation and Construction of Steel Structures-2016 and Turkish Building Earthquake Code-2018. The nonlinear time history analysis method for the sample steel building was made separately for each province considering different earthquake directions, by using the SAP200 program. Records of the 2020 İzmir earthquake (Mw=6.9) were used in the analyses. The displacement, base shear force and moments were obtained for each province for each direction taken into account. The aim of the study is to reveal the effect of both earthquake direction and different seismic regions. The displacement, rotation, base shear force and moment values obtained in the provinces with higher PGA values were also higher. It was determined that the vertical earthquake effect did not significantly change the results obtained for the horizontal direction in this study.